2016
DOI: 10.1111/jbi.12891
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing of rpoB uncovers a significant biogeographical pattern of rhizobial species in soybean rhizosphere

Abstract: Aim Most culture‐independent studies of bacterial biogeography have been at genus or higher taxonomic levels, although many important processes mediated by bacteria are at the strain or species level, such as the competitive nodulation of rhizobia on legumes. Here, at the intra‐species level, we characterized the structural variation in rhizobial populations in soybean rhizosphere under field conditions across 32 sampling sites in three eco‐regions. Location North‐east (Heilongjiang), north (Hebei–Shandong) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…A well-known example of this is the substantial differences in nodulation rates of Sinorhizobium and Bradyrhizobium in soybean grown in soils with different pH values; the differences in the pH tolerance of Sinorhizobium and Bradyrhizobium may explain the geographic distribution patterns of these rhizobia [15,19,22,23]. Comparative genomic analysis revealed that genus-specific genes, known to be involved in alkaline-saline adaptations, likely contribute to the observed biogeographic patterns of Bradyrhizobium and Sinorhizobium nodulation in soybean [24]. Here, we found that the soybean rhizosphere microbiota, especially the B. cereus group, affect the growth and nodulation of Sinorhizobium and Bradyrhizobium, which may also affect the nodulation of these two kinds of rhizobia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-known example of this is the substantial differences in nodulation rates of Sinorhizobium and Bradyrhizobium in soybean grown in soils with different pH values; the differences in the pH tolerance of Sinorhizobium and Bradyrhizobium may explain the geographic distribution patterns of these rhizobia [15,19,22,23]. Comparative genomic analysis revealed that genus-specific genes, known to be involved in alkaline-saline adaptations, likely contribute to the observed biogeographic patterns of Bradyrhizobium and Sinorhizobium nodulation in soybean [24]. Here, we found that the soybean rhizosphere microbiota, especially the B. cereus group, affect the growth and nodulation of Sinorhizobium and Bradyrhizobium, which may also affect the nodulation of these two kinds of rhizobia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the adaptability of these rhizobia to soils with different pH values underlies the biogeographic patterns of soybean root nodulation mediated by Bradyrhizobium and Sinorhizobium [22]. Indeed, Sinorhizobium species are dominant in alkaline-saline soils, whereas Bradyrhizobium are dominant in neutral to acidic soils [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Sinorhizobium fredii predominates Glycine max (cultivated soybean) and G. soja (wild soybean) nodules in the alkaline‐saline soils, while Sinorhizobium sp. III and S. sojae show limited abundance in few sampling sites (Wu et al ., ; Tian et al ., ; Guo et al ., ; Zhang et al ., ). In this study, representative strains of three species SF45436 ( S. fredii CCBAU45436), SS05631 ( S .…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, SF45436 represents the most abundant sublineage of S. fredii, which dominates soybean nodules and rhizospheres in alkaline-saline soils and has a larger accessory genome than Sinorhizobium sp. III (SS05631) and S. sojae (SJ05684) Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation